Complex Twisted Knots of Umbilical Cord in a Monochorionic-Diamniotic Twin Gestation: A Case Report: - Razavi, Behnaz; Kasraeian, Maryam; Hashemi, Atefe; Moradi Alamdarloo, Shaghayegh; Najib, Fateme Sadat (Galen Medical Journal, 2020)
Background: True knots and tight loops of umbilical cord can cause serious fetal complications in monochorionic-monoamniotic twins but are usually unexpected in Monochorionic-diamniotic twins because of the presence of the intertwin membrane. This report presents a case of monochorionic-diamniotic twin gestation with a complex cord knots. Case report: A 31-year-old G2Ab1 with monochorionic-diamniotic twin pregnancy in the gestational age of 30 weeks presented with ruptured membrane since 3weeks before delivery. At the delivery time, multiple umbilical cord knots was found. Conclusion: Premature ruptured membrane can cause septostomy of the intertwin membrane, multiple umbilical cord knots and its complications. Therefore, these cases should be considered for evaluation of the presence of intertwin membrane and umbilical cord knots in each sonography examination. [GMJ.2020;9:e1878]